Investigation of magnetic properties for different coil sizes of dynamic wireless charging pads for electric vehicles (EV) - Zaini, Syasya Azra; Yusoff, Siti Hajar; Abdullah, Amira Aziera; Khan, Sheroz; Abd Rahman, Faridah; Nanda, Nadia Nazieha (IIUM Press, 2020)
: Electric vehicles (EV) have been introduced in the recent years due to public awareness of the effect of gas emission from traditional cars and the extinction of petroleum natural resources. For charging EV, dynamic wireless charging is considered in this paper. This is because it is more convenient and saves charging time since it charges the electric vehicle while moving. The main challenge of this process is to maintain a high amount of power transfer from primary to secondary coil. One of the factors contributing to a good power transfer is the size of the coil [1]. There are various designs of coil for wireless charging of electric vehicles (EV). Among the most common designs are circular pad (CP), rectangular pad (RP), double-D pad (DDP), and double-D quadrature pad (DDQP). In this paper, circular pad (CP) is chosen for use, due to its simplicity in design and good electrical and magnetic properties. Three different coil pair sizes are tested to find the most suitable coil pair for the primary and secondary pads that has the maximum power transfer and is least sensitive to misalignment. The magnetic properties have been investigated to obtain the highest value of magnetic flux. The geometry design of the pads and simulation was done using COMSOL Multiphysics software. From the simulation, it was found that the unsymmetrical coil pair gives high magnetic strength when the outer diameters of the primary and secondary coils have the same value.